The Role of Immunity and Seasonality in Cholera Epidemics - Sanches, Rosangela P. [UNESP]; Ferreira, Claudia P. [UNESP]; Kraenkel, Roberto André [UNESP] (Springer, 2011)
This paper presents a mathematical model for cholera epidemics which comprises seasonality, loss of host immunity, and control mechanisms acting to reduce cholera transmission. A collection of data related to cholera disease allows us to show that outbreaks in endemic areas are subject to a resonant behavior, since the intrinsic oscillation period of the disease (similar to 1 year) is synchronized with the annual contact rate variation. Moreover, we argue that the short period of the host immunity may be associated to secondary peaks of incidence observed in some regions (a bimodal pattern). Finally, we explore some possible mechanisms of cholera control, and analyze their efficiency. We conclude that, besides mass vaccination-which may be impracticable-improvements in sanitation system and food/personal hygiene are the most effective ways to prevent an epidemic.
Keywords: Cholera; Mathematical model; Endemic state; Resonance; Bimodal; Control mechanisms